The Welfare Level Of Oil Palm Harvesting Workers In Air Rami District, Mukomuko Regency - Nabilah Dwi Farisha; Nola Windirah; Agung Trisusilo; Gontom Citoro Kifli (UNIVED Press, Dehasen University Bengkulu, 2025)
Objective: This study aims to analyze the level of welfare and analyze the factors that can affect the level of welfare of smallholder oil palm harvest workers in Air Rami District, Mukomuko Regency. Methodology: This study used Accidental Sampling with the Rao Purba formula, so that 100 respondents were obtained. Data analysis was carried out using the 2023 BKKBN indicators and multinomial logistic regression tests. Results: The results of the study showed that the level of welfare was at several levels of categories, namely in the pre-prosperous family category, prosperous family 1, and prosperous family 2 with the majority being in the prosperous family category 1 of 78%. Factors that can influence are income factors and the number of dependents in the family, while the other 3 factors, namely age, formal education, and work experience of smallholder oil palm harvest workers, do not affect the level of welfare of smallholder oil palm harvest workers. Findings: Many young families have difficulty owning land due to economic limitations, so heads of households choose to work as harvest workers, even though they still face the challenges of welfare without land ownership. Novelty: This study analyzes the welfare of smallholder palm oil harvest workers based on BKKBN indicators. Having a large plantation area, the majority of workers do not have their own land due to economic limitations, so they depend entirely on palm oil harvest work as their main source of income.